Indique uma Mana Goiás: ativismo feminista em grupo de apoio a empreendedoras na internet - Sousa, Ana Carolina de Carvalho (2023)
This research was born from the reflection of the book by bell hooks, “Feminism Is for everybody: Passionate Politics”, when in chapter 9 she brings intersectional aspects of feminism from the point of view of paid work. The object of study researched here is the private group on Facebook “Indique uma Mana Goiás”, composed of women who support each other in the indication of employment and provision of services. In this work, I present my experience in the group through Participant Observation to answer the following question: What are the communication strategies used by women entrepreneurs in a feminist group on the internet? The objective is to analyze the communication strategies used by women entrepreneurs in a feminist group on the internet, under the paradigm of intersectionality, which suggests that we put an end to obedience in gender power relations. With this investigation, I realized that each IUM participant discloses their work according to their knowledge of writing, design or photography. The form varies – from the most rudimentary to the most sophisticated, with a clear communicational objective. However, there is no clear strategy. But one thing is present: the sisterhood in the publications. The sisters are hired because they believe that this movement is necessary in search of financial autonomy among women. They support each other because of a collective conscience of brotherhood. There is no self-definition as feminist in the group's description, but this is the predominant mentality throughout the discussions.